The propagation model of RFID systems in ETC - Weidong Wang; Yinghai Zhang; Wei Yao; Shoufeng Wang (2009 IEEE International Conference on Communication Technology and Applications, 2009)
The propagation model of RFID system in the ETC scenario is different from other wireless systems. In this paper, an ¿N-Ray¿ propagation model that mainly considers the multipath effect is established specialized for RFID systems in ETC. Then simulations are made and the results prove that the model is reasonable.